Mapping the Linguistic Landscape: Geographic Terminology at Geopark Batur Museum - Ni Putu Meri Dewi Pendit; Afriliani Afriliani; Ni Made Verayanti Utami (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Translation is crucial in facilitating cross-cultural understanding, especially in educational and touristic contexts such as museums. In this context, the accurate and acceptable translation of geographic terms is essential to ensure that information remains clear, informative, and culturally relevant for diverse audiences. This study aims to identify various types of geography terms found on the information board at the Batur Volcano Museum, also known as the Geopark Batur Museum. In addition, this study analyzes the most dominant types of terms and their relevance to the museum. The research data was taken from the bilingual informational board with geographic terms in the Geopark Batur Museum. The qualitative method explains the types of geography terms found on the information boards. This analysis is based on the theory of landscape linguistics by Yendra and Artawa (2020) and integrates geography theory, including the theory of geography types by Sinartejo (2019). The results showed five geography terms on the information board: atmosphere, lithosphere, hydrosphere, biosphere, and anthroposphere, with lithosphere as the most dominant type. This is because the museum aims to educate visitors about the geological phenomena that shape the landscape of Batur and its surroundings, so information about the lithosphere is very prominent on the information board. The geographic term lithosphere type refers to information about the rock and soil formations in the region, which are the main attraction for visitors who want to understand the geological uniqueness of Batur. The term lithosphere is therefore very relevant as it covers basic knowledge of the Earth's structure, which is important to understand in geography and geology.